2016
DOI: 10.14236/jhi.v23i3.842
|View full text |Cite
|
Sign up to set email alerts
|

Establishing data-intensive healthcare: the case of Hospital Electronic Prescribing and Medicines Administration systems in Scotland

Abstract: Background Creating learning health systems, characterised by the use and repeated reuse of demographic, process and clinical data to improve the safety, quality and efficiency of care, is a key aim in realising the potential benefits and efficiency savings associated with the implementation of health information technology. Objectives We sought to investigate stakeholder perspectives on and experiences of the implementation of hospital electronic prescribing and medicines administration (HEPMA) systems in Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Out of 952 participants from the two remaining institutions, 477 (50.1%) were female with mean age of 55. 4…”
Section: Study Design and Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 952 participants from the two remaining institutions, 477 (50.1%) were female with mean age of 55. 4…”
Section: Study Design and Populationmentioning
confidence: 99%
“…1,2 A major challenge to achieving this, however, is the recording of high-quality data in electronic health records (EHRs). 3 A recent study by Cresswell et al 4 identified a range of micro-, meso-and macro-level factors that contribute to better use and repeated reuse of demographic, process and healthcare data to improve the quality and safety of care. The lack of motivation and prioritisation by professionals to enter data was identified as key barriers that need to be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported how ePrescribing/CPOE systems enable the generation of, and access to, new data and metrics about individuals, teams, services and organisations9 20 47 62 93 to inform service evaluation and improvement, but with the proviso that appropriate strategies and resources for data monitoring, analysis and follow-up had to be in place to enable improvements 62 92 109…”
Section: Resultsmentioning
confidence: 99%
“…The second paper in this issue is a stakeholder analysis of a prescribing system 3. There are many parallels between the first article and this one.…”
Section: Integrated Systemsmentioning
confidence: 99%